Reorientasi civic disposition dalam kurikulum Pendidikan Kewarganegaraan sebagai upaya membentuk warga negara yang ideal - Mulyono, Budi (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This article discusses the urgency of civic disposition in citizenship education curriculum in order to shape citizen character. Civic disposition is a the most substantive and essential element of citizenship education. In this matter it is intended that good citizen is the target. But, in the course of time, it is evidenced that citizenship education curriculum is intervened by rezim. The feature of a good citizenship means differently to different regime. It is recommended that the reoriented of this curriculum is intended to release the interest and power of rezim by placing Pancasila and 1945 Constitution.